1999
DOI: 10.1007/pl00013750
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of mixed surfactants with polyelectrolytes

Abstract: IntroductionIn most practical applications surfactant mixtures are used rather than a pure species [1]. The reason for this is frequently based on more favorable characteristics of mixtures and the lower cost of production than preparing the individual surfactant components involved. The synergistic properties of mixed surfactants have motivated much of the research in this ®eld [2].Most of the studies on mixed surfactant systems have been concerned with mixed micelle formation and mixed monolayers [3±6]. Litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…The binding isotherm even bent backward a little when the cis compositions increase to 50 and 70% in the mixture. Similar results were also found in our previous works on the binding of TPC and DAC mixture to P(Glu) (13) and on the binding of TPC and DPC mixture to PAMPS (14).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The binding isotherm even bent backward a little when the cis compositions increase to 50 and 70% in the mixture. Similar results were also found in our previous works on the binding of TPC and DAC mixture to P(Glu) (13) and on the binding of TPC and DPC mixture to PAMPS (14).…”
Section: Resultssupporting
confidence: 91%
“…Although there have been published excellent review works on polymer-surfactant systems (9 -12), very few works are referred to in this respect. To overcome this point, we have investigated binary surfactant-polyelectrolyte systems in previous papers and successfully analyzed by the ideal mixing-ideal cooperative binding model; binding of mixtures of tetradecylpyridinium chloride (TPC) and decylammonium chloride (DAC) to poly(L-glutamate) (p(Glu)) and of TPC and dodecylpyridinium chloride (DPC) to PAMPS (13,14). Here it will be shown that the same model is applied to the photosurfactant system together with some insight obtained from the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of electrode has been extensively used by Wyn-Jones et al 48,[54][55][56][57]138,[140][141][142][143][144][145][146][147][148] and by the groups of Shirahama and Hayakawa. 49,[149][150][151][152][153][154] From Table 1, one can see that the polymers are mainly focused on PVP, PEO, PVA, HEUR, CD, MC, NaPA, PAMPS, Chitosan, and triblock-polymers such as Pluronic F68 (EO 76 PO 29 EO 76 ) and F127 (EO 97 PO 69 EO 97 ). [53][54][55][56]74 Anionic surfactants include sodium dodecyl sulfate (SDS), sodium tetradecyl sulfate (STS), etc.…”
Section: Interaction Between Polymers and Ionic Surfactantsmentioning
confidence: 99%
“…With first section of the isotherms for all of the systems investigated, the binding is cooperative, but its strength was found to be dependent on the charge density of PAA in the preformed polyelectrolyte complex aggregates. Subsequently, Shirahama et al 150 have also studied the interactions between a linear polymer PAMPS, and two cationic surfactants, DPyCl and TPyCl and their mixtures with different ratios by a potentiometric titration method using SISEs. By using the ideal mixing/ideal cooperative binding model, they successfully predicted that the binding isotherms of the mixed surfactant systems and the cac of the binding, the binding isotherms and apparent binding isotherms were illustrated in Fig.…”
Section: Interactions Between Polyelectrolytes and Ionic Surfactants ...mentioning
confidence: 99%
See 1 more Smart Citation